Impact of Statutory Retirement Age on the Civil Service System in Kwara State, Nigeria - Isiaka, Sulu Babaita; Kadiri, Ismaila Bolarinwa; Salman, Abdulrazaq; Woli-Jimoh, Ibrahim Ayodeji (NIU Journal of Humanities, 2018)
The problems of fraudulent adjustment of official age by civil servants contained in their personnel record in order to elongate their stay on-the-job beyond the statutory retirement age is a prerequisite for corrupt practices in the civil service. The study therefore examined the effect of Statutory Retirement Age (SRA) of thirty-five years in service on the achievement of government programmes in Kwara State. Descriptive research design method was adopted for the conduct of the study with a population of 13,185. The sample size is 246 respondents. Purposive sampling technique was adopted and Regression Analytical tool was used to test the hypotheses formulated for the study. Data was presented with the aid of inferential statistics of simple percentage table. The result shows that the variability changes in the achievement of government programmes are largely explained by the SRA of thirty-five years in service. Therefore, the study rejected the null hypothesis and accepted the alternative hypothesis that stated that SRA of thirty-five years in service has significant effect on the achievement of government programmes. The study concluded that statutory retirement age has significant effect on civil service system in Kwara State, Nigeria. The study recommended that the Kwara State government should set up a monitoring committee similar to the Quality Assurance Unit in the government house. That the committee should comprise of people, of high integrity both in the private and public sectors, who have excelled in their callings and should report directly to the governors.